Bioturbator‐stimulated loss of seagrass sediment carbon stocks. (27th September 2018) - Thomson, A. C. G.; Trevathan‐Tackett, S. M.; Maher, D. T.; Ralph, P. J.; Macreadie, P. I.
Abstract: Seagrass ecosystems are highly productive, and are sites of significant carbon sequestration. Sediment‐held carbon stocks can be many thousands of years old, and persist largely due to sediment anoxia and because microbial activity is decreasing with depth. However, the carbon sequestered in seagrass ecosystems may be susceptible to remineralization via the activity of bioturbating fauna. Microbial priming is a process whereby remineralization of sediment carbon (recalcitrant organic matter) is stimulated by disturbance, i.e., burial of a labile source of organic matter (seagrass). We investigated the hypothesis that bioturbation could mediate remineralization of sediment carbon stocks through burial of seagrass leaf detritus. We carried out a 2‐month laboratory study to compare the remineralization (measured as CO2 release) of buried seagrass leaves ( Zostera muelleri ) to the total rate of sediment organic matter remineralization in sediment with and without the common Australian bioturbating shrimp Trypaea australiensis (Decapoda: Axiidea). In control sediment containing seagrass but no bioturbators, we observed a negative microbial priming effect, whereby seagrass remineralization was favored over sediment remineralization (and thus preserving sediment stocks). Bioturbation treatments led to a two‐ to five‐fold increase in total CO2 release compared to controls. The estimated bioturbator‐stimulated microbial priming effect was equivalent to 15% of the total daily sediment‐derived CO2 releases. We propose that these results indicate that bioturbation is a potential mechanism that converts these sediments from carbon sinks to sources through stimulation of priming‐enhanced sediment carbon remineralization. We further hypothesized that significant changes to seagrass faunal communities may influence seagrass sediment carbon stocks.